Bisphenol A in Chronic Kidney Disease - Emilio González-Parra; Jose Antonio Herrero; Usama Elewa; Ricardo J. Bosch; Alberto Ortiz Arduán; Jesus Egido (International Journal of Nephrology)
Phenols are uremic toxins of intestinal origin formed by bacteria during protein metabolism. Of these molecules, p-cresol is the most studied and has been associated with renal function impairment and vascular damage. Bisphenol A (BPA) is a molecule with structural similarity with phenols found in plastic food and beverage containers as well as in some dialyzers. BPA is considered an environmental toxicant based on animal and cell culture studies. Japanese authorities recently banned BPA use in baby bottles based on observational association studies in newborns. BPA is excreted in urine and uremic patients present higher serum levels, but there is insufficient evidence to set cut-off levels or to link BPA to any harmful effect in CKD. However, the renal elimination and potential exposure during dialysis warrant the monitoring of BPA exposure and the design of observational studies in which the potential health risks of BPA for end-stage renal disease patients are evaluated.